Pengaruh Penerapan Model Pembelajaran POGIL Berbantuan Media Articulate Storyline terhadap Motivasi dan Hasil Belajar Siswa pada Materi Ikatan Kimia - Siti Maesarah Hasibuan; Jasmidi Jasmidi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The low motivation and learning outcomes of students in chemical bonding material encourages the need for the implementation of innovative learning models assisted by technology. This study aims to determine the effect of the application of the POGIL learning model assisted by Articulate Storyline media on student motivation and learning outcomes in chemical bonding material and to determine the correlation between the two. The research method used is a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 72 students consisting of two classes, namely the experimental class (n = 36) taught with the POGIL model assisted by Articulate Storyline and the control class (n = 36) taught with the direct instruction model assisted by the same media. The research instruments were multiple-choice tests for learning outcomes and Likert scale questionnaires for learning motivation. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, independent sample t-test, and Pearson correlation test. The results showed a significant effect of the POGIL model on student learning motivation (average 81.14 > 67.94) with a significance value of p < 0.05, and on student learning outcomes (average 86.56 > 75.17) with p < 0.05. Furthermore, the Pearson correlation test showed a very strong and significant correlation between motivation and student learning outcomes (r = 0.802; p < 0.05). These findings indicate that the POGIL model, supported by an Articulate Storyline, is a suitable alternative for chemistry learning to improve student motivation and learning outcomes.